Guidelines for tracheostomy in COVID-19 pandemic - Juvekar, Meenesh; Sarkar, Baisali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Measures to be taken by the clinicians involved in doing tracheostomy in light of the recent coronavirus disease, 2019 pandemic are highlighted in current article. Current findings about coronavirus disease, 2019 are evaluated and guidelines to be taken while performing tracheostomy are reviewed. If guidelines for tracheostomy are strictly followed, the probability to get COVID-19 infection drastically reduces. COVID-19 disease has now become pandemic. Many patients admitted in the intensive care require tracheostomy. The aerosol spread of this disease greatly increases the spread and risk of amongst medical and healthcare staff. The protocols for tracheostomy should be clearly defined and followed prior to doing the procedure. This review summarizes the protocols for tracheostomy required to prevent the spread of the disease.